Invulnerable Facts: Infant Mortality and Development in Nationalist Gansu. Issue 4 (1st December 2020) - Hubbard, Joshua A.
Abstract: This article examines responses to high rates of infant mortality in China's northwestern province of Gansu during the Nationalist decades (1927–1949). Based on public health reports for both government and popular audiences, this article argues that the problem of Gansu's especially high infant mortality rate was constructed to serve a particular political and economic agenda, drawing heavily not only from fascist ideals but also the logic of foreign philanthropists and Nationalist technocrats. Once established, the facts of this problem and its cause remained stubbornly invulnerable to new evidence. The article makes two primary contributions. First, it brings to light actors and institutions largely absent in existing scholarship on medicine and public health in Republican China. Second, it cautions against treating infant mortality rates referenced in the historical record as dispassionate measures of life and death. Rather, these purported facts affirm the value ascribed to reproductive health and its relevance for particular political aims.